1990
DOI: 10.3109/00952999009001593
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis of Psychoactive-Substance-lnduced Organic Mental Disorders in Emergency Psychiatry

Abstract: The tendency of emergency psychiatrists to make alcohol- and drug-related diagnoses was examined before and after the addition of a standardized psychoactive substance use questionnaire. The addition of the questionnaire resulted in a significant increase in the number of psychoactive-substance-induced organic mental disorder (substance-induced disorder) diagnoses. The questionnaire selectively increased the recognition of nonalcoholic substance-induced disorders while not significantly increasing the diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Single-center studies report DUD prevalences of 10-18%, substantially higher rates than the 1.9% rate we found [21,22]. Indeed, studies have found that alcohol and other drug use disorders are typically under-diagnosed, even by mental health professionals [23][24][25]. These data support the notion that physicians markedly under-diagnose DUD.…”
Section: Prevalence Of Dud and Distribution Of Implicated Substances supporting
confidence: 74%
“…Single-center studies report DUD prevalences of 10-18%, substantially higher rates than the 1.9% rate we found [21,22]. Indeed, studies have found that alcohol and other drug use disorders are typically under-diagnosed, even by mental health professionals [23][24][25]. These data support the notion that physicians markedly under-diagnose DUD.…”
Section: Prevalence Of Dud and Distribution Of Implicated Substances supporting
confidence: 74%
“…The results suggest the potential benefits of early detection and intervention strategies; however, no research was found to validate this. Several researchers have examined the prevalence of substance abuse amongst psychiatric emergency service users (34)(35)(36)(37)(38). It is evident that substance abuse is prevalent amongst persons receiving psychiatric emergency services; however, nothing is known about appropriate management strategies and their influence on outcomes for this population.…”
Section: Careseeker Characteristicsmentioning
confidence: 99%
“…1Y7,9 In psychiatric emergency settings, the diagnosis of a substance use disorder can be difficult to establish. 10,11 Substanceinduced syndromes may resemble other psychiatric disorders, 8 and self-reporting is often unreliable. 12 Consequently, substance use disorders are often underdiagnosed.…”
mentioning
confidence: 99%